The Role of Religious and Social Values in the Practice of the Sedekah Lang Tradition - Juliani, Sinta; Mustari, Mohammad; Hadi, Muhammad Samsul; Zubair, Muh. (Jurnal Penelitian Medan Agama, 2025)
The Sedekah Lang tradition is a hereditary custom that continues to be maintained and preserved by the community in Tepas Sepakat Village. This research aims to reveal how the implementation of the Sedekah Lang tradition and explore the existence of religious and social values contained in it in Tepas Sepakat Village, Brang Rea District, West Sumbawa Regency. This research uses a qualitative approach with an ethnographic research type. Data collection techniques used observation, interviews and documentation techniques. While the data analysis techniques in this study used data reduction techniques, data presentation techniques, and conclusion drawing. Data validity techniques in this study are triangulation techniques, source triangulation, and time triangulation. Based on the results of the study, it shows that the Sedekah Lang tradition is coupled with activities including 1) pre-event of the Sedekah Lang tradition at this stage including, a) the formation of the committee structure, b) location preparation, c) time set for the event and d) announcement or invitation stage, 2) the course of the Sedekah Lang tradition is divided into several stages including the a) opening stage, b) remarks, c) lectures by religious leaders, d) prayers and dhikr, and e) closing. Apart from that, there is the existence of religious and social values contained in the implementation of the Sedekah Lang tradition in Tepas Sepakat Village.